Penggunaan Biokoagulan Dari Biji Tanaman Untuk Menurunkan Kekeruhan Pada Air Sungai - Olivia, Arinda; Darmayanti, Lita; Fitria, Dewi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The problem that is often found in raw water sources, namely surface water or river water, is that it tends to have high turbidity concentrations. This turbidity is basically caused by particles that are difficult to settle. One method that can be used to remove turbidity in water is the coagulation and flocculation processes. This study aims to determine the biocoagulant ability of papaya seeds to reduce turbidity in river water, by varying the dose of coagulant 0.2 gr / l; 0.4 gr / l; 0.6 gr / l; 0.8 gr / l; 1.0 gr / l and 1.2 gr / l. The results obtained showed that the highest turbidity removal was at a coagulant dose of 0.6 gr / l with an efficiency of 87.42%. Keywords: coagulation and flocculation, biocoagulant, papaya seeds, turbidity